2014
DOI: 10.1111/liv.12452
|View full text |Cite
|
Sign up to set email alerts
|

Drugs plus ligation to prevent rebleeding in cirrhosis: an updated systematic review

Abstract: Background & Aims: Combined therapy with endoscopic variceal ligation (EVL) and b-blockers ± isosorbide mononitrate (ISMN) is currently recommended to prevent variceal rebleeding. However, the role of this combined therapy has been challenged by some studies. We performed a systematic review to assess the value of combined therapy with EVL and b-blockers ± ISMN as compared with each treatment alone to prevent rebleeding. Methods: Databases, references and meeting abstracts were searched to retrieve randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 44 publications
6
85
1
3
Order By: Relevance
“…A recent meta-analysis comparing combination therapy to monotherapy with EVL or drug therapy has demonstrated that, when compared to EVL, combination therapy is significantly more effective in preventing all-source GI hemorrhage. However, combination therapy is only marginally more effective than drug therapy (NSBB ± nitrates) alone with a tendency for an increased survival with drugs alone [9] . This suggests that pharmacological therapy is the cornerstone of combination therapy and that EVL should not be used as sole therapy in the prevention of recurrent hemorrhage.…”
Section: Variceal Hemorrhagementioning
confidence: 99%
“…A recent meta-analysis comparing combination therapy to monotherapy with EVL or drug therapy has demonstrated that, when compared to EVL, combination therapy is significantly more effective in preventing all-source GI hemorrhage. However, combination therapy is only marginally more effective than drug therapy (NSBB ± nitrates) alone with a tendency for an increased survival with drugs alone [9] . This suggests that pharmacological therapy is the cornerstone of combination therapy and that EVL should not be used as sole therapy in the prevention of recurrent hemorrhage.…”
Section: Variceal Hemorrhagementioning
confidence: 99%
“…Overall, there was a trend towards lower rebleeding (RR = 0.76, 95% CI = 0.58-1.00) without effect on mortality (RR = 1.24, 95% CI = 0.90-1.70). 27 The risk for all-cause deaths in the EVL group was significantly higher than in the medical group [RR 1.25 (95% CI 1.01 to 1.55)]; however, the rate of bleeding related deaths was unaffected [RR 1.16 (95% CI 0.68 to 1.97)]. 26 In the present study subjects, who had decompensated cirrhosis with Child Pugh Score >12 were excluded to avoid higher mortality in the treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials [5,22,27,35,37,42] were multicenter trials. Beta-blockers were administrated in 9 trials, including nadolol used in 6 trials [5,6,12,27,35,41] and propranolol in the other 3 [20,24,42]. Followup time of 4 trials [23,33,40,42] was less than 3 months, but there were 15 RCTs followed up for 1 year or more.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The investigators agreed to exclude octreotide and sclerotherapy plus octreotide from our study since octreotide is rarely used nowadays, especially for non-ER patients. Finally, 26 eligible RCTs [5,6,12, involving 2,536 adults were incorporated into our quantitative network meta-analysis. A flowchart summarizing the entire search process and resultant reports is provided in Figure 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation